Identification of creep damage properties of coating via a compound miniaturized testing method and an inverse approach - Ming Li; Xiaoyi Shi; Xiufang Gong; Wu Wen; Xu Xu; Zhixun Wen; Zhufeng Yue; Wei Sun; Shan-Tung Tu (Journal of Materials Research and Technology, 2024)
A systematic analytical approach has been developed to comprehensively characterize the creep damage material properties of coatings on thin-layer substrates. This involves conducting creep tests using a compound, two-material, miniaturized thin plate specimen (MTPS) with an inverse approach. For demonstration, independent creep tests were performed on miniature specimens of the substrate (P91 steel) and the coating (CoNiCrAlY) at 650 °C, as well as on compound substrate-coating specimens. The reference stress method, coupled with finite element analysis, was utilized to obtain conversion parameters for strain data from the miniature specimen tests. Analytical solutions for the Kachanov creep damage model specific to the two-material substrate-coating system were adopted for inverse optimization. The MTPS testing method and the associated inverse approach have proven effective in accurately determining the complete three-stage creep constants within the coating-substrate system. Results obtained for the P91–CoNiCrAlY coated system have shown a clear demonstration of the accuracy and capability of the method in identifying the full sets of uniaxial creep damage properties, i.e. A, n, m, B, χ, and φ, provided the feasible experimental data are available.